E-learning in context: An assessment of student inequalities in a university outreach program - Crawford, Nicole; McKenzie, Lara (Australasian Journal of Educational Technology, 2011)
E-learning technologies are often seen as a driving force in the democratisation of contemporary education. However, few researchers have focused on inequalities in online learners' access to technologies or their abilities to use them. In 2009, we assessed The University of Western Australia's SmARTS outreach program, investigating the advantages and disadvantages of employing online learning in the local context of Perth, Western Australia. SmARTS uses blended learning techniques, combining both online and face to face methods. However, our discussion here is based primarily on the online component. Our research methods included the collection of 52 student surveys, a group interview with the 2009 tutors, and our own observations and experiences. Our findings suggested that students were not particularly savvy with technology, in contrast to the common assumption. We also found that the location of students' residences and the types of schools they attended had an impact on their self-assessed online participation, the reliability and speed of their Internet connections, and their confidence and ease with using computers and the Internet. Our findings revealed that the social inequalities present in the context of Perth had an impact on whether students were advantaged or disadvantaged by the online component of SmARTS.